FAKTOR – FAKTOR YANG MEMPENGARUHI KEPATUHAN PENGOBATAN HIPERTENSI PADA LANSIA BINAAN PUSKESMAS KLUNGKUNG 1 - Pratama, Gede Wahyu; Ariastuti, Ni Luh Putu (E-Jurnal Medika Udayana; vol 4 no 8(2015):e-jurnal medika udayana, 2015)
FACTORS THAT AFFECTING HYPERTENSION TREATMENTS COMPLIANCE ON ELDERLY AT KLUNGKUNG 1 PUBLIC HEALTH CENTRE Based on data from 2014, hypertension is one of the diseases that included in the top 10 diseases in Klungkung 1 PHC. Interviews with health workers in Klungkung 1 PHC shows that there are still elderly with hypertension who are not adherent to the treatment. It certainly requires appropriate care. Identifying the factors that influence the compliance of hypertension treatment in elderly is the first step that needs to be done. This study is a cross-sectional analytical study with all elderly hypertensive patients (?45 years) who came for treatment and recorded at Klungkung 1 PHC in 2014 as study population. Samples were obtained by calculating the minimum sample size and performed simple random sampling to obtain 97 samples. Data obtained by structured interviews and direct observation. The data analysis was done by using univariate and bivariate analyzes. Results of this study are: from the 97 samples, 62 (63.9%) samples had low adherence and 36.1% of the sample had a high adherence to the treatment of hypertension. Statistical test results on the factors that affect adherence showed significant result on; the level of knowledge (p = 0.015), motivation (p = 0.02), support from health worker (p = 0.048) and family support (p = 0.000). While the number of drugs types consumed (p = 0.485) and access to health care services show insignificant results.
Keywords: Compliance, Hypertension